Tax Incentives for use of Alternative Energy Sources in the Russian Federation - Ponomareva, Nadezhda V.; Zvereva, Anna O.; Golubtsova, Ekaterina V.; Ilyashenko, Svetlana B. (International Journal of Energy Economics and Policy, 2019)
Increasingly widespread use of alternative energy sources solves a number of urgent state problems, such as reduction of environmental pollution, diversification of energy resources, and weakening the dependence of the budget on oil revenues. The present article considers the role of taxes in the economic motivation of production and the use of alternative energy sources, as well as analyzes world practices of tax regulation in consumption of energy from renewable natural resources. In the course of the study, methods of collecting and processing secondary information were used, namely, grouping, generalization, classification, systematization, and modeling. In order to optimize the use of the proposed tax instruments, the latter are grouped according to the category of taxpayers. Keywords: power industry, alternative energy sources, government control, taxes JEL Classifications: H23, Q29, Q57 DOI: https://doi.org/10.32479/ijeep.7964